2017
DOI: 10.1515/mms-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Signal Strength Mapping and Analysis by Means of Mobile Geographic Information System

Abstract: Bluetooth beacons are becoming increasingly popular for various applications such as marketing or indoor navigation. However, designing a proper beacon installation requires knowledge of the possible sources of interference in the target environment. While theoretically beacon signal strength should decay linearly with log distance, on-site measurements usually reveal that noise from objects such as Wi-Fi networks operating in the vicinity significantly alters the expected signal range. The paper presents a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Thus, the accuracy of EC interpolations would be limited; at least until a sufficiently large and spatially varied infection dataset is collected. It should be noted, however, that there are no technical obstacles in the way of implementing this functionality in the future, as it has been shown that data interpolation in DHTML can work well even on a relatively weak client hardware (Kulawiak & Wycinka, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the accuracy of EC interpolations would be limited; at least until a sufficiently large and spatially varied infection dataset is collected. It should be noted, however, that there are no technical obstacles in the way of implementing this functionality in the future, as it has been shown that data interpolation in DHTML can work well even on a relatively weak client hardware (Kulawiak & Wycinka, 2017 ).…”
Section: Discussionmentioning
confidence: 99%